Pengaruh Perputaran Persediaan, Perputaran Kas, Perputaran Piutang, dan Profitabilitas Terhadap Harga Saham Perusahaan Agricultural Periode 2021 – 2023 - Lukman, Karyn; Luki, Katherine Yuan; Dini, Siti; Hasibuan, Muhammad Zulkifli (Soratekno Publisher, 2025)
Indonesia has a capital market that plays a significant role in the country's economy. Investors with excess funds can invest in various financial instruments in the hope of generating returns. Meanwhile, companies in need of capital can utilize these funds to develop their business projects. The purpose of this study is to examine the effect of inventory turnover, cash turnover, receivables turnover, and profitability on stock prices in agricultural companies during the period of 2021–2023. This study uses all agricultural companies listed on the Indonesia Stock Exchange as the population, totaling 24 companies. The sample used in this research consists of 57 observational data points. The research results, both partially and simultaneously, indicate that inventory turnover, cash turnover, receivables turnover, and return on assets (ROA) have a positive and significant effect on stock prices of agricultural companies listed on the Indonesia Stock Exchange in 2021–2023. The Adjusted R Square value is 0.437 or 43.7%, which means that 43.7% of the variation in stock prices can be explained by the variables of inventory turnover, cash turnover, receivables turnover, and return on assets. The remaining 56.3% is explained by other variables not examined in this study, such as return on equity and liquidity.